Adaptations in pediatric anesthesia care and airway management in the resource‐poor setting. Issue 3 (27th January 2020) - Manyumwa, Petros; Chimhundu‐Sithole, Tsitsi; Marange‐Chikuni, Danai; Evans, Faye M.
Abstract: The need for safe and quality pediatric anesthesia care in low‐ and middle‐income countries (LMICs) is huge. An estimated 1.7 billion children do not have access to surgical care, and the majority are in LMICs. In addition, most LMICs do not have the requisite surgical workforce including anesthesia providers. Surgery is usually performed at three levels of facilities: district, provincial, and national referral hospitals. Unfortunately, the manpower, equipment, and other resources available to provide surgical care for children vary greatly at the different level facilities. The majority of district level hospitals are staffed solely by non‐physician anesthesia providers with variable training and little support to manage complicated pediatric patients. Airway and respiratory complications are known to account for a large portion of pediatric perioperative complications. Management of the difficult pediatric airway pathology is a challenge for anesthesia providers regardless of setting. However, in the low‐resource setting poor infrastructure, lack of transportation systems, and crippled referral systems lead to late presentation. There is often a lack of pediatric‐sized anesthesia equipment and resources, making management of the local pathology even more challenging. Efforts are being made to offer these providers additional training in pediatric anesthesia skills that incorporate low‐fidelity simulation. Out of necessity, anesthesia providers in this setting learn to be resourceful in order to manage complex pathologies with fewer, less ideal resources while still providing a safe anesthetic.